2006
DOI: 10.1007/s00402-006-0143-4
|View full text |Cite
|
Sign up to set email alerts
|

Two cannulated hip screws for femoral neck fractures: treatment of choice or asking for trouble?

Abstract: In conclusion, the results of this study show that in case of operative treatment, undisplaced femoral neck fractures can be adequately fixated by two cannulated hip screws. Unstable, anatomically reduced femoral neck fracture (Garden III/IV) may be treated with a more stable implant (e.g. DHS) to avoid redisplacement. If adequate reduction cannot be achieved, endoprosthetic replacement is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 21 publications
0
28
0
3
Order By: Relevance
“…10 Kauffman, sin embargo, demostró que es necesario un cuarto tornillo cuando hay conminución posterior en el cuello femoral. 18 Por otro lado, la fijación con 2 tornillos resulta suficiente en fracturas no desplazadas, 33,34 mientras que, en las fracturas desplazadas, es necesario utilizar, por lo menos, 3 tornillos. 33 De todas formas, Parker y Blundell, en un metanálisis que incluyó 4925 pacientes, encontraron imposible determinar el número y la configuración óptima de los tornillos.…”
Section: 18-20unclassified
“…10 Kauffman, sin embargo, demostró que es necesario un cuarto tornillo cuando hay conminución posterior en el cuello femoral. 18 Por otro lado, la fijación con 2 tornillos resulta suficiente en fracturas no desplazadas, 33,34 mientras que, en las fracturas desplazadas, es necesario utilizar, por lo menos, 3 tornillos. 33 De todas formas, Parker y Blundell, en un metanálisis que incluyó 4925 pacientes, encontraron imposible determinar el número y la configuración óptima de los tornillos.…”
Section: 18-20unclassified
“…Krastman et al (9) concluded that for non-dislocated fractures (Garden I and II), only two cannulated screws are sufficient to obtain consolidation. In the normal technique using three screws, it is recommended that the screws be place perpendicular to each other.…”
Section: Comparison Of Volumes Occupied By Different Internal Fixatiomentioning
confidence: 99%
“…The problem does not lie with the Classification itself. For instance, Krastman, et al [13] established a Pauwels Grade II as 30° to 70°, and allocated 71% of 112 cases as Grade II injuries. In contrast, Prinčič, et al [5] identified only 7.1% of 351 cases as Pauwels Grade II injuries.…”
Section: Copyright © 2010 Scires Jbisementioning
confidence: 99%
“…Many authors use the Pauwels [1] as well as the Garden [16] Classifications to evaluate the respective risks of non-union or femoral head necrosis and to determine the best mode of treatment [2,7,13,19,20].…”
Section: Copyright © 2010 Scires Jbisementioning
confidence: 99%